Synthesis, characterization, molecular docking, ADMET prediction, and anti-inflammatory activity of some Schiff bases derived from salicylaldehyde as a potential cyclooxygenase inhibitor (Baghdad Science Journal, 2023)
A series of Schiff base-bearing salicylaldehyde moiety compounds (1-4) had been designed, synthesized, subjected to insilico ADMET prediction, molecular docking, characterization by FT-IR, and CHNS analysis techniques, and finally to their Anti-inflammatory profile using cyclooxygenase fluorescence inhibitor screening assay methods along with standard drugs, celecoxib, and diclofenac. The ADMET studies were used to predict which compounds would be suitable for oral administration, as well as absorption sites, bioavailability, TPSA, and drug likeness. According to the results of ADME data, all of the produced chemicals can be absorbed through the GIT and have passed Lipinski’s rule of five. Through molecular docking with PyRx 0.8, these synthesized compounds were tested insilico selectivity toward COX-1 and COX-2 and in vitro for their anti-inflammatory efficacy . In vitro testing demonstrated that all of the produced compounds had significantly stronger activity against the COX-2 enzyme than COX-1. Among these, compound 1 displayed the most potent inhibitory activity with an IC50 value of 0.19 µM compared to standard drug celecoxib (IC50 = 0.29 µM). The most active derivative compound1 was oriented towards the active site and occupied the target enzyme based on the docking investigation against COX-1 and COX-2. In addition, insilico investigations found that COX-2 has a higher inhibitory activity than COX-1